The Relevance of Forming Evaluation Criteria of Moral and Values Aspects of Educational Resources in Modern Conditions on the example of Ethno-Cultural Component - Абдигапбарова, Улжаркын; Амреева, Т. (Pedagogy and Psychology, 2022)
The Republican Scientific conducted this research and Practical Center for Educational Content Expertise together with the National Academy of Education named after Y. Altynsarin of the Ministry of Education and Science of the Republic of Kazakhstan as part of the program-targeted financing of the research OR 11465474 "Scientific foundations of modernization of the education system and science". The article presents the result analysis of scientific, methodological and practical research results of the moral-values aspects of educational resource content on the example of ethno-cultural component. It is established that technical methods of evaluation influence both the content of an education program or resources and further ways of their implementation. Principles and criteria for evaluating the ethno-cultural component in the educational resources are determined.